Effect of potassium levels in the severity of bacterial wilt in common bean cultivars. - Theodoro, Gustavo de Faria; Maringoni, Antonio Carlos [UNESP] (My University, 2006)
The objective of this work was to evaluate the effect of potassium (K) levels in the bacterial wilt severity in three bean cultivars (IAC Carioca Pyatã, IPR 88-Uirapuru and SCS 202-Guará), under gree-nhouse conditions. The treatments were 135.0, 112.5, 90.0, 67.5 and 45.0 kg.ha-1 of K2 O, using potassium chloride. The evaluations were performed at 5, 10, 15, 20 and 25 days after the inoculation and it was estimated the area under the bacterial wilt progress curve (AUBWPC). Neither the AUBWPC nor the K content in the aerial part of the IAC Carioca Pyatã and IPR 88-Uirapuru cultivars were affected by the K2 O levels. As K2 O levels increased, the dry mass weight also incre-ased, but only in the non-inoculated plants of the SCS 202 – Guará cultivar.
Efeito de doses de potássio na severidade da murcha-de-curtobacterium em cultivares de feijoeiro comum
Keywords: Bacteria; Curtobacterium flaccumfaciens pv. flaccumfaciens; Mineral nutrition; Phaseolus vulgaris; Potassium chloride